Privatisation in Poland after 1989 - Kaliński, Janusz (Studia Historiae Oeconomicae, 2011)
The author of the article takes up the task of offering the overall assessment of Polish privatisation, looking at the processes of privatisation in the context of their implications for business and for the economy as a whole. For that purpose, he refers, among other things, to the different paths of privatisation adopted within the analysed process of privatisation and discusses the role of foreign capital. The author is also interested in the economic efficiency and social consequences of privatisation until 2008.